Exploring the relationships among attachment, emotional intelligence and communication. Issue 3 (8th February 2013) - Cherry, M Gemma; Fletcher, Ian; O'Sullivan, Helen
<x xml:space="preserve">Abstract</x> Objectives Attachment style has been shown to influence both emotional intelligence (EI) and the clinical communication of medical students and doctors. No research has assessed the relationships among attachment, EI and clinical communication in medical students. This study was conducted to evaluate the effect of EI on the relationship between medical students' attachment style and clinical communication. Methods Medical students were invited to complete measures of attachment (using the Experiences in Close Relationships–Short Form [ECR‐SF], a 12‐item measure that provides attachment avoidance and attachment anxiety dimensional scores) and EI (using the Mayer–Salovey–Caruso Emotional Intelligence Test [MSCEIT], a 141‐item measure of the perception, use, understanding and management of emotions) at the end of Year 1, prior to a summative objective structured clinical examination (OSCE). Clinical communication was assessed using OSCE scores. Structural equation modelling (SEM) was used to analyse a hypothetical model of the relationships among attachment style, EI and clinical communication. Results A total of 200 of 358 (55.9%) students participated. Attachment avoidance was significantly negatively correlated with total EI scores (r = − 0.28, p < 0.01); total EI was significantly positively correlated with OSCE scores (r = 0.23, p < 0.01). A parsimonious SEM revealed that attachment avoidance accounted for 13% of the variance in students' total EI scores but did not directly predict OSCE scores, whereas total EI significantly predicted 7% of the variance in OSCE scores. Conclusions Attachment is perceived to be stable from early adulthood, whereas the literature suggests that EI can be developed through the use of targeted interventions. This has potential implications for the training of medical students in clinical communication.